2015
DOI: 10.3390/life5031539
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Temperature and Growth Phase on the Lipidomes of Sulfolobus islandicus and Sulfolobus tokodaii

Abstract: The functionality of the plasma membrane is essential for all organisms. Adaption to high growth temperatures imposes challenges and Bacteria, Eukarya, and Archaea have developed several mechanisms to cope with these. Hyperthermophilic archaea have earlier been shown to synthesize tetraether membrane lipids with an increased number of cyclopentane moieties at higher growth temperatures. Here we used shotgun lipidomics to study this effect as well as the influence of growth phase on the lipidomes of Sulfolobus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
66
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(85 citation statements)
references
References 50 publications
(116 reference statements)
9
66
1
Order By: Relevance
“…This finding is consistent with Jensen et al (2015) who showed a dip in the ring index in cells of S. islandicus and S. tokodaii harvested during log phase relative to those harvested during lag or stationary phase. These observations suggest that actively growing crenarcheotes (e.g., S. islandicus and S. tokodaii ) and euryarcheotes (e.g., P. torridus ) produce GDGTs with fewer cyclopentyl rings and that less active cells produce GDGTs with more rings.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with Jensen et al (2015) who showed a dip in the ring index in cells of S. islandicus and S. tokodaii harvested during log phase relative to those harvested during lag or stationary phase. These observations suggest that actively growing crenarcheotes (e.g., S. islandicus and S. tokodaii ) and euryarcheotes (e.g., P. torridus ) produce GDGTs with fewer cyclopentyl rings and that less active cells produce GDGTs with more rings.…”
Section: Discussionsupporting
confidence: 93%
“…We further examine, for the first time, the impact of agitation on GDGT cyclization. Higher temperatures yielded higher average cyclization, which is consistent with most experimental studies of both Thaum- and Crenarchaeota (912, 24, 25), yet opposes recent environmental findings in alkaline hotsprings (26). When pH deviated from the optimum pH of ∼3 for DSM639, cyclization decreased.…”
Section: Discussionsupporting
confidence: 87%
“…Growth rate and ring index broadly covary, independent of which variable is causing this forcing (Figure 4). The temperature, pH and shaking speed experiments show inverse trends between growth rate and RI, consistent with batch experiments in the existing Thaumarchaeota (Figure S1) and Crenarchaeota (Figure S2) literature (11, 12, 29). However, these trends directly oppose results from other experiments characterizing GDGT response to pH in thermoacidophiles (11).…”
Section: Discussionsupporting
confidence: 85%
“…phosphate, inositol phosphate, glycerol phosphate, phospho-glycerol-phosphate or ethanolamine phosphate with one to four hexoses), also sulfonated tri-hexosylglycerol dialkyl glycerol tetraether-inositol phosphate . Another similar study carried out by shotgun analysis focused on the effects of rising temperatures at which archaea grow an increasing number of cyclopentane moieties in the membranes of S. islandicus and Sulfolobus tokodaii (Jensen, Neesgaard, et al, 2015). Elling et al (2014) dealt with the effects of the growth phase on the membrane lipid composition of the thaumarchaeon Nitrosopumilus maritimus and their implications for archaeal lipid distributions by LC-MS in the marine environment.…”
Section: ) Lipidsmentioning
confidence: 99%
“…phosphate, inositol phosphate, glycerol phosphate, phospho‐glycerol‐phosphate or ethanolamine phosphate with one to four hexoses), also sulfonated tri‐hexosyl‐glycerol dialkyl glycerol tetraether‐inositol phosphate (Jensen, Brandl, Treusch, & Ejsing, ). Another similar study carried out by shotgun analysis focused on the effects of rising temperatures at which archaea grow an increasing number of cyclopentane moieties in the membranes of S. islandicus and Sulfolobus tokodaii (Jensen, Neesgaard, et al, ).…”
Section: Introductionmentioning
confidence: 99%